Smart and Connected: Esports Centers as Urban Social Hubs for Smart Cities - Purba, Paul Aldo; Sembiring , Dicky Andrea (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Amidst the swift progression of technology and the rising demand for interactive urban spaces, esports centers have emerged as promising platforms for actualizing the vision of smart cities and communities. This research investigates how the spatial design of esports centers can effectively integrate smart city principles and strengthen community bonds within urban environments. Through an innovative design approach, this study conceptualizes esports centers as multifunctional spaces beyond gaming arenas. By leveraging information technology, smart lighting, and eco-friendly materials, these centers are designed to provide an inviting and comfortable environment for visitors. The incorporation of digital connectivity, social spaces, and sustainability zones into the interior design aims to ensure an immersive gaming experience while encouraging social interaction. The findings of this research demonstrate that designing esports center spaces in alignment with smart city concepts can create environments that support gaming activities and foster collaboration and interaction among visitors. Therefore, this research offers a new perspective on the potential of esports centers as integral components of smart cities, emphasizing the crucial role of spatial design in developing connected and sustainable communities